2021
DOI: 10.1371/journal.pone.0247652
|View full text |Cite
|
Sign up to set email alerts
|

Harmine inhibits breast cancer cell migration and invasion by inducing the degradation of Twist1

Abstract: Breast cancer is the leading cause of cancer-related deaths in the United States. The majority of deaths (90%) in breast cancer patients is caused by invasion and metastasis–two features related to the epithelial-to-mesenchymal transition (EMT). Twist1 is a key transcription factor that promotes the EMT, which leads to cell migration, invasion, cancer metastasis, and therapeutic resistance. Harmine is a beta-carboline alkaloid found in a variety of plants and was recently shown to be able to induce degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…In recent years, harmine has been reported to elicit a series of anti‐cancer activities, but the detailed mechanism remains obscure (Dai et al, 2012; He et al, 2022; Nafie et al, 2021; Uhl et al, 2018; Wu et al, 2019; Zhang et al, 2014; Zhu et al, 2021). In this study, we report that harmine can activate ER stress, resulting in the up‐regulation of DR5 and SESN2, which promotes apoptosis and autophagosome formation in KYSE‐30 and EC‐9706 cells, respectively (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, harmine has been reported to elicit a series of anti‐cancer activities, but the detailed mechanism remains obscure (Dai et al, 2012; He et al, 2022; Nafie et al, 2021; Uhl et al, 2018; Wu et al, 2019; Zhang et al, 2014; Zhu et al, 2021). In this study, we report that harmine can activate ER stress, resulting in the up‐regulation of DR5 and SESN2, which promotes apoptosis and autophagosome formation in KYSE‐30 and EC‐9706 cells, respectively (Figure 9).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that harmine and its derivatives exhibit anti‐cancer activities via the regulation of cyclooxygenase‐2, Twist1, FAK/Akt, p53, and MAPK, among other pathways (Dai et al, 2012; Nafie et al, 2021; Ock & Kim, 2021; Zhang et al, 2014; Zhu et al, 2021). In KYSE‐30 and EC‐9706 cells, harmine down‐regulated the phosphorylation of AMPK, Akt, and mTOR (Figure 6), which are downstream targets of SESN2 and play key roles in regulating autophagic responses (Ibanez‐Cabellos et al, 2018; Kma & Baruah, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmine inhibits the growth of different cancer cell types (e.g., ovarian and gastric cancer). 95 It is able to prevent tumor development, metastasis, and triggering apoptosis and possess anti-cancer capabilities. The pharmacological effects of harmine include antifungal, antibacterial, antiplasmodial, antioxidant, cytotoxic, antitumoral, hallucinogenic and antimutagenic action.…”
Section: Harmine (Beta-carboline Alkaloid)mentioning
confidence: 99%
“…A beta‐carboline alkaloid (Figure 4) with a wide dissemination in nature is called as harmine. Harmine inhibits the growth of different cancer cell types (e.g., ovarian and gastric cancer) 95 . It is able to prevent tumor development, metastasis, and triggering apoptosis and possess anti‐cancer capabilities.…”
Section: Introductionmentioning
confidence: 99%